P237 Comparison of COPD exacerbations with once-daily QVA149 versus twice-daily salmeterol/fluticasone combination: the ILLUMINATE study. (14th November 2013) - Vogelmeier, C; Bateman, ED; Chen, H; Banerji, D
Abstract : Introduction: Exacerbations are the most frequent cause of hospitalisation and death among patients with COPD. Combinations of long-acting bronchodilators maximise bronchodilation and may reduce the risk of exacerbations. QVA149, a once-daily dual bronchodilator containing the long-acting β2 agonist (LABA) indacaterol and long-acting muscarinic antagonist (LAMA) glycopyrronium, improves lung function, breathlessness and rescue medication use compared with twice-daily salmeterol/fluticasone combination (SFC), in patients with moderate-to-severe COPD. 1 Methods: In this 26-week, multicenter, double-blind study, patients ≥ 40 years with COPD (forced expiratory volume in 1 second [FEV1 ] ≥40% to <80% predicted and no history of exacerbations in the previous year) were randomised (1:1) to QVA149 110/50 µg or SFC 50/500 µg. In this post hoc analysis, we report the rate of mild, moderate or severe COPD exacerbations during 26 weeks of treatment with QVA149 or SFC. Results: Of 522 patients randomised [QVA149 (n = 258), SFC (n = 264); mean age: 63.3 years; mean post-bronchodilator FEV1 : 60.2% predicted], 82.6% completed. Rate ratio of QVA149 versus SFC [RR] of moderate or severe exacerbations was 0.80 (95% confidence interval [CI]: 0.41–1.56) and for all COPD exacerbations (mild, moderate, and severe), RR was 0.69 (95% CI: 0.44–1.07) (neither statistically significant). Conclusion: Risk of exacerbations with once-daily QVA149 was numerically, but not statistically significantly, lower than twice-daily SFC in patients with moderate-to-severe COPD and no previous history of exacerbations. The LABA/LAMA combination QVA149 has the potential to be an alternative to LABA/ICS in preventing COPD exacerbations. Reference: Vogelmeier et al . Lancet Respir Med 2013;1(1):50–60.